Collaborative-Based Web Recommender System for Homestay Program: A Bridging tool in a Tourism Supply Chain - Ramli, Razamin; Miraz, Mahadi Hasan; Ku Mahamud, Ku-Ruhana; Omar, Mohd Faizal; Kayat, Kalsom (International Journal of Supply Chain Management, 2019)
Abstract - Homestay Program (HP) initiatives play an important role in Community-based Tourism (CBT), especially for Malaysian tourism industry. HPs offer activities that are catalysts to the community development, focusing those in the rural areas. However, due to technological advancements, promotion and marketing strategy for the unique CBT initiative needs a new and inventive move.Â This leads to the proposed technology-based framework for a system as part of the specific CBT supply chain (CBTSC), known as the Collaborative-based Web Recommender (CBWR) system or simply, website. The CBTSC is further intensified to emerge the CBWR sub-supply chain model. As part of the CBWR model, the CBWR website is able to essentially promote the CBT effort of HP worldwide, thus supports community development and livelihood.Â Keywords - Homestay Program, Collaborative-Based Web Recommender System, Community-Based Tourism Supply Chain, Technology-Based Promotion and Marketing, Rural Community-Based Tourism